Identifikasi Kandungan Unsur Mineral Pada Area Bekas Tambang Emas Placer Dengan Metode X-Ray Fluorescence - Ferdinandus Ferdinandus; I Putu Putrawiyanta; Novalisae; Noveriady Noveriady; Immanuel Nababan; Matius Yosefhin (G-Tech: Jurnal Teknologi Terapan, 2024)
The lack of knowledge and technology in small-scale community gold mining means that many concentrations of other valuable mineral elements cannot be identified and retrieved. This research aims to determine the remaining elemental content in former small-scale community gold mining areas. The research method is by taking leftover mining material at the research location and then preparing and analyzing it using the X-ray Fluorescence (XRF) method. The research results from the 9 sample points taken showed that the concentrations of the elements Si (Silica) and Fe (Iron) were the most dominant with an average value of Silica (Si) 85% and Iron (Fe) 7.37%. It can be concluded that at the research location there are still other mineral elements of economic value besides gold that are not mined and utilized.